Genetic Influences on Physiological and Subjective Responses to an Aerobic Exercise Session among Sedentary Adults. (29th July 2012) - Karoly, Hollis C.; Stevens, Courtney J.; Magnan, Renee E.; Harlaar, Nicole; Hutchison, Kent E.; Bryan, Angela D.
Abstract : Objective . To determine whether genetic variants suggested by the literature to be associated with physiology and fitness phenotypes predicted differential physiological and subjective responses to a bout of aerobic exercise among inactive but otherwise healthy adults. Method . Participants completed a 30-minute submaximal aerobic exercise session. Measures of physiological and subjective responding were taken before, during, and after exercise. 14 single nucleotide polymorphisms (SNPs) that have been previously associated with various exercise phenotypes were tested for associations with physiological and subjective response to exercise phenotypes. Results . We found that two SNPs in the FTO gene (rs8044769 and rs3751812) were related to positive affect change during exercise. Two SNPs in the CREB1 gene (rs2253206 and 2360969) were related to change in temperature during exercise and with maximal oxygen capacity (VO2 max). The SLIT2 SNP rs1379659 and the FAM5C SNP rs1935881 were associated with norepinephrine change during exercise. Finally, the OPRM1 SNP rs1799971 was related to changes in norepinephrine, lactate, and rate of perceived exertion (RPE) during exercise. Conclusion . Genetic factors influence both physiological and subjective responses to exercise. A better understanding of genetic factors underlying physiological and subjective responses to aerobic exercise has implications for development and potential tailoring of exercise interventions.